Ethnobotany of the Sierra Nevada del Cocuy-Güicán: climate change and conservation strategies in the Colombian Andes - Mireia Alcántara Rodríguez; Andrea Angueyra; Antoine M. Cleef; Tinde Van Andel (BMC, 2018)
Abstract Background The Sierra Nevada del Cocuy-Güicán in the Colombian Andes is protected as a National Natural Park since 1977 because of its fragile páramo ecosystems, extraordinary biodiversity, high plant endemism, and function as water reservoir. The vegetation on this mountain is threatened by expanding agriculture, deforestation, tourism, and climate change. We present an ethnobotanical inventory among local farmer communities and discuss the effects of vegetation change on the availability of useful plants. Methods We used 76 semi-structured, 4 in-depth interviews, and 247 botanical collections to record the ethnoflora of the farmers and surveyed from the high Andean forest to the super-páramo, including native and introduced species. We organized 3 participative workshops with local children, high school students, and campesinos' women to share the data we acquired in the field and empower local plant conservation awareness. Results We encountered 174 useful plants, most of them native to the area (68%) and almost one third introduced (32%). The Compositae was the most species-rich family, followed by Lamiaceae, Poaceae, and Rosaceae. The majority of plant species were used as medicine, followed by food, firewood, and domestic tools. Local farmers reported declining numbers of páramo species, which were now only found at higher altitudes than before. Although our informants were worried about the preservation of their natural resources and noticed the effects of climate change, for several commercial species, unsustainable land use and overharvesting seemed to be the direct cause of declining medicinal plant resources rather than climate change. Conclusions We recommend conservation plans that include vegetation monitoring, people's perceptions on climate change, and participative actions with the communities of the Sierra Nevada del Cocuy-Güicán.